The detaxation of overtime hours: lessons from the French experiment - Cahuc, Pierre; Carcillo, Stéphane (London, 2011)
"In October 2007 France introduced an exemption on the income tax and social security contributions that applied to wages received for hours worked overtime. The goal of the policy was to increase the number of hours worked. This article shows that this reform has had no significant impact on hours worked. Conversely, it has had a positive impact on the overtime hours declared by highly qualified wage-earners, who have opportunities to manipulate the overtime hours they declare in order to optimize their tax situation, since the hours they work are difficult to verify."